KERAGAMAN GENETIK AKSESI EKINASE (Echinacea purpurea (L.) Moench) HASIL SELEKSI MASSA TAHUN I MELALUI ANALISIS RAPD - Subositi, Dyah; Widiyastuti, Yuli (Buletin Kebun Raya, 2013)
Ekinase (Echinacea purpurea (L.) Moench) a medicinal plant that has immunostimulatory activity. This plant has been cultivating in Tawangmangu region by Medicinal Plant and Traditional Medicine Research and Development Office since 2002. Ten accessions of E. purpurea were found based on their morphological variation, three accessions of them are selected as promising accessions namely BH2, BHU3 dan BHU5. The objective of this research was to observe the genetic diversity ofÂ  thoseÂ  promising accessions and 8 variants accession from mass selection year I using RAPD analysis. Those accessions were amplified using 10 RAPD primers. A total of 64 scorable fragments were generated from 9 RAPD primers, among which 48 fragments (75%) were polymorphic. The Dice coefficient was used to calculated the genetic similarity and UPGMA was used to generate the dendogram. The genetic similarity index among accessions evaluated ranged from 75,49-84,21% thus indicating that low level of genetic diversity. RAPD analysis proved to be efficient for genetic diversity of ekinase accessions from mass selection year I.